SAT0411 Cognitive and Emotional Processing in Systemic Lupus Erythematosus: An FMRI Study. (9th June 2015) - Barraclough, M.; Elliott, R.; McKie, S.; Parker, B.; Bruce, I.
Abstract : Background: Cognitive dysfunction (CD) is a common aspect of Systemic Lupus Erythematosus (SLE) and the exact cause is often unclear. Functional magnetic resonance imaging (fMRI) is a technique used in many other conditions and provides sensitive measures of brain functionality during cognitive tasks. Previous fMRI studies in SLE show that in spite of unimpaired behavioural performance, patients with SLE employ compensatory brain mechanisms to maintain adequate cognitive function [1-3]. Depression and anxiety are also more frequently reported in SLE patients than in the general population [4] and it is well known that mood disorders can significantly affect cognitive function. Objectives: This study aims to explore functional brain differences between SLE participants and healthy controls during cognitive and emotional processing. Methods: 11 SLE participants who met ACR criteria and 9 healthy controls, mean ages of 36.5 (14.9) and 40.0 (12.6) years respectively, undertook a working memory task (n-back) and a facial emotional recognition task (FERT) during fMRI. The n-back task had three levels (0-, 1- and 2-back) with the 2-back level being the most difficult. The FERT displayed faces expressing different emotions: happiness, sadness, fear and neutral. Both tasks were analysed using region of interest (ROI) analysis in SPM12. Results: Participants were well matched on key variables. The SLE group had mean disease duration of 12.6 (9.1) years and mean SLEDAI of 5.1 (3.8). There were no differences in behavioural responses to the tasks however there were significant differences in the average blood-oxygen-level dependent (BOLD) signal extracted from the ROI. During the n-back task, 2- vs 0-back condition, SLE participants had an increased BOLD response in the middle frontal gyrus (MFG) ( p =0.04). SLE participants also had an increased BOLD response in the amygdala when processing sadness vs neutral ( p =0.01) during the FERT (see figure 1 .). Conclusions: As previously described, SLE participants had an increased BOLD response to the n-back task in frontal regions during cognitive processing. This may indicate that SLE participants utilise compensatory mechanisms to maintain adequate cognitive function. SLE participants also had an increased response in emotional processing areas when viewing sad faces. Research with depressed patients has shown this to be a potential biomarker for depression [5] which may be of importance for SLE participants. Future analysis of increased participant numbers will control for variables such as mood, medication and disease activity. References: DiFrancesco et al., Arthritis Research & Therapy 2013, 15(2):R40. Mak et al., Seminars in Arthritis & Rheumatism 2012, 41(6):849-858. Mackay et al., Molecular Medicine 2011, 17(11-12):1349-1356. Uguz et al., Comprehensive Psychiatry 2013, 54(4):341-345. Arnone et al., The American Journal of Psychiatry 2012, 169(8):841-850. Acknowledgements: Prof. Bruce is funded by ARUK, the NIHR Manchester BRU and The NIHR Manchester WTCRF. Prof. Elliott and Dr McKie are supported by the NIHR Manchester BRU. Dr Parker is supported by the NIHR Manchester BRU and The NIHR Manchester WTCRF. Mrs Barraclough is funded by the NIHR Manchester BRU and Genzyme Sanofi. Disclosure of Interest: M. Barraclough Grant/research support from: Genzyme Sanofi, NIHR Manchester BRU, R. Elliott Grant/research support from: Genzyme Sanofi, NIHR Manchester BRU, S. McKie Grant/research support from: Genzyme Sanofi, NIHR Manchester BRU, B. Parker Grant/research support from: Genzyme Sanofi, NIHR Manchester BRU, I. Bruce Grant/research support from: Genzyme Sanofi, NIHR Manchester BRU